Manufacturing change and policy response in the contemporary economic landscape: how cities in Ontario, Canada, understand and plan for manufacturing. Issue 1 (1st January 2019) - Cleave, Evan; Vecchio, Marcello; Spilsbury, Duncan; Arku, Godwin
ABSTRACT: Despite its nearly half-century decline in Western countries, manufacturing remains a vital part of local and regional economies. This importance is reflected in the economic development policies of cities, which are struggling to understand the current state of manufacturing and what they should do to either reinforce or replace it. Within the scholarship and practice, however, there is limited understanding of the policies that are adopted and whether they have potential to have a meaningful impact for the cities that adopt them. To address this gap, this research considers the way that manufacturing is contextualized and responded to within the local economic development planning documents of 47 (of 51) cities in Ontario, Canada. Through a comprehensive content analysis, it examines whether there are variations in the way cities approach manufacturing. Based on chi-square analysis, the findings show that there is considerable homogeneity in the way that cities of all sizes are approaching manufacturing, suggesting they are not adequately considering the local context in their policy, and rather focus on more general and previously adopted approaches. However, there is an emerging spatiality to the policy that was identified, which presents cities with a pathway forward to address manufacturing within their local economic development.